Estrategias lúdicas y su influencia en el desarrollo de habilidades cognitivas en los infantes de 4 a 5 años de educación inicial en la Unidad Educativa Francisco Huerta Rendón cantón Babahoyo - Ortiz Domínguez, Edith Maday (2023)
The application of ludic strategies, with the passage of time, has become a topic of discussion due to its various advantages and disadvantages, within what is established in the national curriculum, which reveals the educational model that speaks of constructivism, and is given to know the different and new curricular approaches that seek to give a twist to that traditional education that, unfortunately, is still used by certain teachers who are reluctant to the changes that society demands. The role that teachers have been fulfilling has changed radically because they have experienced the need to adapt to new educational models, identify learning styles and rhythms in order to successfully meet the needs of society. It is imperative to understand the importance of cognitive development in infants, since it is in this process that they acquire knowledge through learning and experience from the first years of life. It should be noted that cognitive abilities include various disciplines and abilities such as perception, memory, problem solving, etc., all of them unique functions that people acquire from childhood and over the years.